(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
This article explores the concept of servant leadership as a modern leadership model that combines serving others with achieving organizational goals. The core idea is that leadership is not based on authority or control, but rather on providing support and empowerment to individuals, fostering positive interaction and creating a more humane and productive work environment. The article discusses key principles of servant leadership, such as altruism, active listening, building trust, promoting employee personal growth, and achieving organizational justice. It also illustrates the impact of this leadership approach on improving job satisfaction, supporting innovation, and strengthening organizational loyalty. The article concludes that servant leadership represents an effective contemporary vision for organizations seeking to develop ethical leadership styles that align with modern transformations in work environments. This article aims to analyze the concept of servant leadership as a contemporary trend in modern management thought by reviewing the theoretical foundations of this leadership model, discussing its core principles, and examining its impact on organizational environments. The article adopts an analytical approach that focuses on the most prominent practices of servant leadership, including employee empowerment, active listening, individual capacity building, and promoting trust and justice within the organization. The findings indicate that adopting servant leadership contributes to increased job satisfaction, improved performance quality, and greater organizational commitment, making it a suitable leadership approach for addressing modern management challenges. The article concludes that servant leadership represents an advanced vision that transcends traditional models, providing a humanistic and ethical framework that enhances organizational effectiveness in the current era.